Digital Evidence in Criminal Trials: Challenges in Adversarial vs Inquisitorial Systems - Jenora Kwaning (Universal Institute of Professional Management, 2025)
This paper examines how digital evidence is handled in criminal trials within adversarial and inquisitorial legal systems. It compares the two models in terms of evidence collection, admissibility standards, and the role of Judges and lawyers in evaluating digital material. Key issues such as chain of custody, authenticity, privacy concerns, and procedural fairness are analyzed through relevant case law and legal commentary.